Dampak Pancasila Terhadap Pertumbuhan Moral dan Etika di Kalangan Generasi Z - Aisyah Tsabitah Ulayya; Adly Muhammad Mahdy; Fadzar Rambu Alam; Muhamad Zaqi Rafliansyah; Herli Antoni (Student Research Journal, 2024)
Generation Z as the nation's successor faces moral and ethical challenges during rapid globalization and technological development. This condition raises concerns about the decline in awareness of the noble values of Pancasila, which are the basis of community life. This research aims to analyze the impact of Pancasila values on the moral and ethical growth of Generation Z and explore the optimal strategy to internalize these values in their lives. With a literature study method, this study examines various relevant literature related to the role of Pancasila, morals, ethics, and characteristics of Generation Z. The results of the study show that Pancasila values, such as social justice, humanity, and cooperation, play an important role in shaping the morals and ethics of Generation Z. These values can be a relevant ethical guide to dealing with moral problems, both in the real and digital world. However, the influence of social media and global culture is a major challenge in maintaining their morality. Therefore, an innovative approach is needed in internalizing the values of Pancasila. The role of family, school, and community is very important in building Pancasila-based character. Education based on these noble values needs to be applied to support Generation Z so that they are not only technologically literate, but also have strong moral integrity.